2020
DOI: 10.1111/jocn.15500
|View full text |Cite
|
Sign up to set email alerts
|

Disruption, worries and autonomy in the everyday lives of adolescents with type 1 diabetes and their family members: A qualitative study of intrafamilial challenges

Abstract: Aim: To explore daily life with type 1 diabetes in families with an adolescent with type 1 diabetes. Background: Management of adolescent type 1 diabetes is carried out in the context of everyday life, thus involving and affecting the entire family. Type 1 diabetes causes disruption of family life, but the specific experiences and challenges of adolescents with type 1 diabetes, siblings and parents are not well-explored. Specifically, research is lacking on the siblings' experience of adolescents with type 1 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 41 publications
3
26
0
Order By: Relevance
“…The results of our study showed that young people with less diabetes-related worry had better SMBG adherence, consistent with a study on young people with T1DM in the U.S. 27 The literature suggested that a high level of diabetes-related worry can contribute to anxiety, 59 which can impose a cognitive burden on an adolescent with T1DM. Subsequently, young people tend to ignore diabetes management tasks (eg, SMBG).…”
Section: Discussionsupporting
confidence: 91%
“…The results of our study showed that young people with less diabetes-related worry had better SMBG adherence, consistent with a study on young people with T1DM in the U.S. 27 The literature suggested that a high level of diabetes-related worry can contribute to anxiety, 59 which can impose a cognitive burden on an adolescent with T1DM. Subsequently, young people tend to ignore diabetes management tasks (eg, SMBG).…”
Section: Discussionsupporting
confidence: 91%
“…Across all workshops, the same tools were used to facilitate dialogue among adolescents with T1D [22,24,25]. Author DG participated in all workshops, confirming that participants were presented with the same topics.…”
Section: Methodsmentioning
confidence: 84%
“…Five of the workshops originate from a study exploring intervention needs among families with a 13-to 18-year-old with T1D in a rural area of Denmark, the aim being to improve the overall diabetes approach at the local pediatric diabetes clinic [24]. Three of the workshops originate from an unpublished study exploring daily life with diabetes among 13-to 18-year-olds and their families, investigating the role of important relations in diabetes management.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the International Society for Pediatric and Adolescent Diabetes, the overall goal and purpose of diabetes treatment is "to provide care that results in high quality of life, normal growth and development, and lowest attainable risk of acute and long-term diabetes complications" [2]. Nevertheless, when a child is diagnosed with T1D the whole family is faced with chronic disruption [3,4] and increased risk of poor mental health [5,6]. The onset of T1D has numerous consequences for family life.…”
Section: Introductionmentioning
confidence: 99%